Understanding The Complexity Of University Management: A Review Of Higher Education Organization Theory - ., J. (Universiti Sains Islam Malaysia, 2024)
Higher education/university takes on an essential function in society. According to the Indonesian Constitution No. 20/2003 on National Education System, the university has three principal functions, known as Tri Dharma, which encompasses education, research and social services. Through this, the Indonesian university is expected to be an agent of change to create competent and qualified graduates. Besides, university should also become a leading research institution where different innovations can be created to bring significant contribution to social development. For this purpose, the present article sets to examine how the organization of university in its endeavours to achieve Tri Dharma goal fits with relevant theory. A qualitative research was carried out amongst 15 senior university lecturers in Banten. Participants were interviewed and their responses have been incorporated into this article. The results show that the Javanese culture influences both the formal and informal structures of Indonesian universities.